Pengaruh Pengangguran, IPM, dan Pertumbuhan Sektor Industri terhadap Kemiskinan di 9 Kota di Provinsi Jawa Timur - Elmawati, Fitri; Suparta, I Made (Widya Balina, 2025)
A recent study analyzed the factors influencing poverty rates in nine cities in East Java from 2020 to 2024, with a specific focus on the unemployment rate, Human Development Index (HDI), and industrial sector growth. Utilizing secondary panel data and a Random Effect Model (REM) for analysis, the research yielded significant insights: higher unemployment positively and significantly correlates with increased poverty, whereas improved HDI levels lead to a significant reduction in poverty. Interestingly, despite growth, the industrial sector's impact on poverty reduction was found to be insignificant. Therefore, policy recommendations stemming from this study highlight the crucial need for proactive measures to curb unemployment, continuous efforts to enhance human resource quality through HDI initiatives, and strategies to ensure industrial growth more directly translate into job creation and improved community well-being..